The Rise of the Major Religions - Makhlouf, Georgia; Moeller, Walter O.; Welply, Michaël (Englewood Cliffs, N.J : Silver Burdett, 1988)
Explores the origins, history, customs, and beliefs of the world's major religions, including Judaism, Christianity, Islam, Hinduism, and Buddhism.
Translation of: Les grandes religions. Maps on lining papers.
Includes bibliographical references and index.
Keywords: Religions -- Juvenile literature; Dinler -- Çocuk edebiyatı; Religions; Dinler